Принцесса из собачьей будки - Ланская Елизавета (Люди-маугли, 2014)
Экземпляры: ф-6 (20220203) / Инвентарный номер: 57874 / Цена: 80.00 / Сис.шифр: Р2 / Авт.знак: Л 22 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6